(untitled) (Communications in Computational Physics, 2020)
Water management is a key to ensuring high performance and durability of polymer electrolyte fuel cell (PEFC), and it is important to understand the behavior of liquid water in PEFC. In this study, the two-phase lattice Boltzmann method is applied to the simulations of water discharge from gas diffusion layers (GDL) to gas channels. The GDL is porous media composed of carbon fibers with hydrophobic treatment, and the gas channels are hydrophilic micro-scale ducts. In the simulations, arbitrarily generated porous materials are used as the structures of the GDL. We investigate the effects of solid surface wettabilities on water distribution in the gas channels and the GDL. Moreover, the results of X-ray computed tomography images in the operating PEFC are compared with the numerical simulations, and the mechanism of the water transport in PEFC is considered.